Arctic offshore oil and gas concerns: maritime law, sustainable development and human rights : a brief look at Iceland & Greenland - Guðmundur Egill Erlendsson (2010)
Arctic offshore oil and gas activities are increasing with an expeditious rate in the last years, oil and gas exploitations are on the rise and just recently Iceland joined the other eight states in preparing for these kinds of undertakings. The international legal framework is proving to be fragmented when it comes to dealing with these types of activities and potentially the environment of the Arctic is not being adequately safeguarded. Here the question of whether there are international standards for oil and gas exploitations in the Arctic as a whole or are there just general frameworks. The United Nation Convention on the Law of the Sea sits at the heart of the Regional cooperation as well as international standards is surveyed; a perspective is set on the impact some driving factors such as the economies of the Arctic from the non- renewable resource exploitations angle. Some light is shed on the term Sustainable Development and its connection to the non-renewable resource exploitation. But then a focus on the human factor in all these endeavours by discussing human rights and an attempt at a linkage of sustainable development with the international human rights framework is made. Where the right to development and the rights to a healthy environment are indeed a third generation of human rights and irrefutably intermingled with these types of resource use. An overview of Iceland and Greenland in the offshore oil and gas exploitations and comparison on various practical points of interest such as taxation and the differences in practise between the two countries.